2015
DOI: 10.1093/jnci/djv034
|View full text |Cite
|
Sign up to set email alerts
|

The Role of BPTF in Melanoma Progression and in Response to BRAF-Targeted Therapy

Abstract: Background:Bromodomain PHD finger transcription factor (BPTF) plays an important role in chromatin remodeling, but its functional role in tumor progression is incompletely understood. Here we explore the oncogenic effects of BPTF in melanoma.Methods:The consequences of differential expression of BPTF were explored using shRNA-mediated knockdown in several melanoma cell lines. Immunoblotting was used to assess the expression of various proteins regulated by BPTF. The functional role of BPTF in melanoma progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 42 publications
(43 reference statements)
5
67
0
Order By: Relevance
“…Our prior analysis showed that BPTF activates the MAP kinase pathway by regulating ERK expression at the transcriptional level (11). Taken together, these studies demonstrate that BPTF is involved in multiple signaling pathways critical to melanoma proliferation and survival.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Our prior analysis showed that BPTF activates the MAP kinase pathway by regulating ERK expression at the transcriptional level (11). Taken together, these studies demonstrate that BPTF is involved in multiple signaling pathways critical to melanoma proliferation and survival.…”
Section: Discussionmentioning
confidence: 74%
“…Recent studies identified an oncogenic role for BPTF in melanoma progression, and described a role both in the prediction and promotion of melanoma distant metastasis (11). BPTF mediated its proproliferative and pro-oncogenic effects by regulating the expression of prosurvival genes, such as BCL2, BCL-XL, and CCND2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BPTF is required for MAPK and PI3K/AKT signaling and the survival of lung cancer cells (46). BPTF is also important for cell proliferation through interaction with c-Myc in fibroblasts and melanoma cells (47, 48). Since MAPK, PI3K/AKT and c-Myc dependent pathways can regulate T cell function (4951), it is plausible that one or more of these pathway(s) is perturbed in the absence of BPTF in T cells.…”
Section: Discussionmentioning
confidence: 99%
“…1 Clinical trials are underway evaluating inhibition of several members of the bromodomain and extra terminal family (BET) bromodomains (i.e, Brd2, 3, 4) in cancer, diabetes, and inflammation, supporting bromodomain modulation as a potential therapeutic approach. 2 The bromodomain PHD finger transcription factor, BPTF, is thought to play a significant role in melanoma, 3 leukemia, 4 colorectal, 5 and bladder cancer 6 . Both the PHD finger and bromodomain are important for chromatin binding.…”
Section: Introductionmentioning
confidence: 99%